2022
DOI: 10.3390/plants11131667
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiling and Antibacterial Activity of Methanol Leaf Extract of Skimmia anquetilia

Abstract: Skimmia anquetilia is a plant species native to the Western Himalaya region that has tremendous potential for phytochemical activities. This study aimed to identify bioactive compounds and assess the antibacterial activity of S. anquetilia. To determine the major bioactive chemicals in the methanol leaf extract of S. anquetilia, we used a gas chromatography–mass spectrometer (GC-MS). The presence of 35 distinct phytoconstituents was discovered using GC-MS, which could contribute to the therapeutic capabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
(30 reference statements)
2
7
0
Order By: Relevance
“…In this study, the root extracts of S. anquetilia exhibited remarkable invitro antibacterial potential towards the gram-positive and gram-negative bacterial strains by inhibiting their colony and growth rate, which is the first report from this study. Recently, Nabi et al (2022a) reported the antibacterial potential of methanol leaf extract of S. anquetilia against P. aeruginosa, E. coli, K. pneumoniae, S. typhi, and S. aureus. Previously, the antimicrobial activity using the essential oil extracted from S. laureola was documented (Jangwan et al, 2010;Irshad et al, 2012).…”
Section: Organic Extract Concentration (Mg MLmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the root extracts of S. anquetilia exhibited remarkable invitro antibacterial potential towards the gram-positive and gram-negative bacterial strains by inhibiting their colony and growth rate, which is the first report from this study. Recently, Nabi et al (2022a) reported the antibacterial potential of methanol leaf extract of S. anquetilia against P. aeruginosa, E. coli, K. pneumoniae, S. typhi, and S. aureus. Previously, the antimicrobial activity using the essential oil extracted from S. laureola was documented (Jangwan et al, 2010;Irshad et al, 2012).…”
Section: Organic Extract Concentration (Mg MLmentioning
confidence: 99%
“…Some studies suggest that around 25,000 of the original plant-specific preparations are available in indigenous folk and conventional medicine systems that are recommended by approximately 15 lakh folk healers for preventive, convincing, and curative purposes (Sen and Chakraborty, 2015). Essential oils and crude extracts of medicinal plants possess numerous kinds of bioactive compounds that have revealed an array of bioefficacies, namely antibacterial (Zeb et al, 2016;Umaru et al, 2019;Nabi et al, 2022a), antifungal (Banaras et al, 2020), antianalgesic (Lisa et al, 2020), antioxidant (Gondwal et al, 2012a;Umaru et al, 2019), anticancerous (Liu Y. T. et al, 2020;Oh et al, 2020), antidiabetic (Tran et al, 2020), etc. S. anquetilia (Rutaceae) is an erect, perennial, glabrous, scented, creeping gregarious, ornamental shrub, 1.5 m in height, found in association with conifers between 1,800 and 2,715 m above msl in Western Himalaya.…”
Section: Introductionmentioning
confidence: 99%
“…The highest zone of inhibition (12.6 ± 0.8) was exhibited by methanol extract against A. tumifaciens ( Sharma et al, 2008a ). Recently, ( Nabi et al, 2022a , b ) reported the antibacterial activity of methanol leaf extract and n -hexane, ethyl-acetate, and methanol root extracts of S. anquetilia against Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae, Salmonella typhi , and Staphylococcus aureus at different concentrations (10, 20, 40, 80, and 160 mg/ml) using the agar well diffusion assay. The methanolic leaf extract showed the highest zone of inhibition against E. coli (19.0 ± 0.57), followed by P. aeruginosa (18.0 ± 0.57) and K. Pneumoniae (17.0 ± 0.57) at 160 mg/ml.…”
Section: Pharmacology Of S Anquetiliamentioning
confidence: 99%
“…Various active compounds viz , alkanes, alkenes, coumarins, carboxylic acids, fatty acids, and esters of fatty acids, terpenes (monoterpenes, diterpenes, sesquiterpenes), etc., have been reported to be the major bioactive compounds in this plant ( Bhatt et al, 2021 ). The varied bioactivities including anti-arthritic ( Verma et al, 2020 ), anticancer ( Wani et al, 2016 ), anti-inflammatory, antibacterial ( Nabi et al, 2022a , b ), antioxidant, and anti-feedant ( Gondwal et al, 2015 ) activities have been studied with potential findings. Despite the positive outcome, most of the studies are based on the in-vitro models and mechanisms of action are not well-studied.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Other studies proposed the valorization of different plants from their leaves [ 9 , 10 , 11 , 12 ]. Early studies on the valorization of guayule by-products focused on the extraction of essential and volatile oils from stem resin [ 13 , 14 ], while more recent attention was paid to phenolic compounds [ 7 , 15 , 16 ], particularly hydroxycinnamic and hydroxybenzoic acids, flavones, flavanols and anthraquinones [ 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%